Integrating primary care, shared decision making, and community engagement to facilitate equitable access to multi-cancer early detection clinical trials - Thompson, Cheryl L.; Buchanan, Adam H.; Myers, Ronald; Weinberg, David S. (Frontiers in Oncology, 2024)
Effective implementation of cancer screening programs can reduce disease-specific incidence and mortality. Screening is currently recommended for breast, cervical, colorectal and lung cancer. However, initial and repeat adherence to screening tests in accordance with current guidelines is sub-optimal, with the lowest rates observed in historically underserved groups. If used in concert with recommended cancer screening tests, new biospecimen-based multi-cancer early detection (MCED) tests could help to identify more cancers that may be amendable to effective treatment. Clinical trials designed to assess the safety and efficacy of MCED tests to assess their potential for reducing cancer mortality are needed and many are underway. In the conduct of MCED test trials, it is crucial that participant recruitment efforts successfully engage participants from diverse populations experiencing cancer disparities. Strategic partnerships involving health systems, clinical practices, and communities can increase the reach of MCED trial recruitment efforts among populations experiencing disparities. This goal can be achieved by developing health system-based learning communities that build understanding of and trust in biomedical research; and by applying innovative methods for identifying eligible trial patients, educating potential participants about research trials, and engaging eligible individuals in shared decision making (SDM) about trial participation. This article describes how a developing consortium of health systems has used this approach to encourage the uptake of cancer screening in a wide range of populations and how such a strategy can facilitate the enrollment of persons from diverse patient and community populations in MCED trials.